Contemporary Research on E-business Technology and Strategy International Conference, iCETS 2012, Tianjin, China, August 29-31, 2012, Revised Selected Papers - Khachidze, Vasil; Wang, Tim.; Siddiqui, Sohail; Liu, Vincent; Cappuccio, Sergio; Lim, Alicia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the International Conference on E-business and Strategy, iCETS 2012, held in Tianjin, China, in August 2012. The 65 revised full papers presented were carefully reviewed and selected from 231 submissions. The papers feature contemporary research on developments in the fields of e-business technology, information management systems, and business strategy. Topics addressed are latest development on e-business technology, computer science and software engineering for e-business, e-business and e-commerce applications, social networking and social engineering for e-business, e-business strategic management and economics development, e-business education, entrepreneurship and e-learning, digital economy strategy, as well as internet and e-commerce policy.
e-business technology -- computer science and software engineering for e-business -- e-business and e-commerce applications -- social networking and social engineering for e-business -- e-business strategic management and economics development -- e-business education -- entrepreneurship and e-learning -- digital economy strategy -- internet and e-commerce policy.
Keywords: Computer science; Database management; Information storage and retrieval systems; Information Systems; Computer Science; Management of Computing and Information Systems; e-Commerce/e-business.; Information Systems Applications (incl. Internet).; Computers and Society; Information Storage and Retrieval; Database Management